Prevalence of ovarian cysts in production high cows under containment system and diet total - Motta, Rodrigo Garcia; Martins, Lorrayne de Souza Araújo; Medeiros, Gustavo Silva; Junior, Valdir Chiogna (Revista de Ciências Agroveterinárias, 2019)
This study aimed to evaluate the follicular cysts prevalence in high production dairy cows, post-partum, under total diet regime in three different systems: Compost Barn, Free Stall and opened feedlot. There were evaluated 1600 cows, HPB, seven flocks, of which 792 (49.5%) were empty and late in the reproductive protocols. The examination sonographic ovarian score was distributed as: Score 1 (61.4%), Score 2 (18,1) Score 3 (4.0%) and Cystic Ovary (16.5%). As for the production system the cysts prevalence were 16% in Free Stall, 17.2% in Compost Barn and 16.2% in opened feedlot, without significant difference. 84.7% (n = 131) of animals were in anestrus in the presence of diagnosis follicular cyst. 60.7% of animal with follicular cysts were 60 to 180 days postpartum. Divided in 27.5% between 60 and 90 days, 24.5% between 91 and 120 days, 15.5% between 121 and 150 days and 32.5% between 151 and 500 postpartum. The cysts prevalence according to lactation number were: 29.8% in first, 26.7% in second, 24.4% in third, 5.3% in fourth, 4.6% in fifth and 9.2% in sixth, statistically significant results to higher cysts occurrence in the first three lactations. For body condition score 62.6% of animals with ovarian cyst were with scores from 2.0 to 2.5, 25.2% with a score of 2.6 to 3.0 and 12.2% with score of 3.1 to 4.0 also significant results. Where the chance of cows with low body score develop cysts was 5.1 times higher compared to animals with good score. Follicular cysts present high prevalence in high producing dairy cows, impacting sub-fertility and causing important damage in global dairy farming, thus, it is necessary further studies for the development of more effective preventive measures to control this situation.